2014
DOI: 10.1371/journal.pone.0104159
|View full text |Cite
|
Sign up to set email alerts
|

PCB153-Induced Overexpression of ID3 Contributes to the Development of Microvascular Lesions

Abstract: Microvascular lesions resulting from endothelial cell dysfunction are produced in the brain, lung, kidney, and retina of patients of complex chronic diseases. The environmental and molecular risk factors which may contribute in the development of microvascular damage are unclear. The mechanism(s) responsible for initiating microvascular damage remain poorly defined, although several inciting factors have been proposed, including environmental toxicants-induced oxidative stress. Enhanced neovascularization has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 50 publications
(51 reference statements)
2
25
0
Order By: Relevance
“…We reported that both E2 and PCB153 induced ID3 phosphorylation. E2 treatment stabilized ID3 protein during the 1–6 h treatment time points and increased phosphorylated ID3 levels [10, 21]. It was noteworthy that we showed data of ID3 tyrosine phosphorylation by PCB153 treatment which was confirmed by MALDI-TOF MS/MS spectra data.…”
Section: Inhibitor Of Dna Binding/differentiation-3 (Id3)supporting
confidence: 72%
“…We reported that both E2 and PCB153 induced ID3 phosphorylation. E2 treatment stabilized ID3 protein during the 1–6 h treatment time points and increased phosphorylated ID3 levels [10, 21]. It was noteworthy that we showed data of ID3 tyrosine phosphorylation by PCB153 treatment which was confirmed by MALDI-TOF MS/MS spectra data.…”
Section: Inhibitor Of Dna Binding/differentiation-3 (Id3)supporting
confidence: 72%
“…Similarly, Id-3 (inhibitor of differentiation protein 3) has been proven to be equally responsible in inducing the endothelial dysfunction due to its significance in reactive-oxygen species (ROS)-induced cellular proliferation of the endothelial cells. Recent studies have concluded the active involvement of Id3 in the development of microvascular lesions in various organs (including the retina of the eye) in people suffering from complex chronic disorders [7]. In case of diabetic retinopathy, the newly generating blood vessels (due to the process of neovascularization) get highly affected by the overexpression of Id-1 and Id-3, which are well known to be responsible for poor vascularization.…”
Section: Endostatin Is Responsible For the Downregulation Of Id1 And Id3mentioning
confidence: 99%
“…In family of Id proteins, the helix-loop-helix motif is the site of interaction which results in the dimerisation of Id proteins with the basic helix-loop-helix transcription factors. These events result in the negative regulation of the transcription process and are also responsible for the process of neovascularization [7].…”
Section: Endostatin Is Responsible For the Downregulation Of Id1 And Id3mentioning
confidence: 99%
“…Since many of these vascular remodeling mechanisms are oxidative stress dependent [4] [8][9][10]. Based on recent findings that demonstrated ID3 dependent endothelial cell activation via estrogenic PCB153 exposure, we will discuss how exposure to estrogenic endocrine disruptors (EEDs) may contribute to complex vascular lesions, in which cardiopulmonary disease manifest from via ID3 [11]. Previously, we elucidated association between ID3 & EEDs in metabolic syndrome (MetS) perturbations via adipose tissue that bioaccumulate, which can modify various chronic diseases such as vascular, neurological, cancer, and autoimmune [12][13].…”
Section: Introductionmentioning
confidence: 99%